Drug utilization pattern of antimicrobial agent used in ear, nose and throat outpatient and inpatient department at tertiary care teaching centre - Arora, Renu; Upadhyay, Sumit; Singh, Hukum; Bajpai, Anurag (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The prospective, observational study was designed to assess the prescribing pattern of drug usage in ENT Department in various diseases conditions. Methods: Medication utilization Form has been designed based on a WHO format. The patient’s details including patient particulars, diagnosis, investigations, drug details and information regarding the indication for prescribing agents. Patient were enrolled those are either gender with age more than 20 years, outpatients and in patients who are treated in ENT department and who are diagnosed as acute and chronic disease. Exclusion criteria were below the age of 20 years, the patients who were not willing to take antimicrobial agents and those were not able to give consent were excluded. Results: Total 1021 prescriptions were analysed, 38.5% were males and 61.5% were females, respectively. 319 of patients were diagnosed with ear, 157 with nose and 489 with throat disorders. The most common disease reported was CSOM in 134 patients and least were only one patient with myringitis. The most frequently prescribed antibiotics were β-lactams was commonly prescribed and least were nitroimidazoles. In the concomitant medications, aceclofenac and serratiopeptidase were most commonly prescribed and least were pantoprazole and domperidone. Conclusions: Prescribing pattern of usage of antibiotics are more compared to other drugs, β Lactams antibiotics are most commonly prescribed antibiotics in various ENT diseases, usage of brand name are higher than the generic name.